Renewable energy : power for a sustainable future - Peake, Stephen (Oxford University Press in association with the Open University, 2018)
"An interdisciplinary approach brings together economic, social, environmental, and policy issues to give you a holistic view of this multi-faceted subject area. Chapters explore the full range of renewable energy technologies, including: solar thermal; solar photovoltaics; bioenergy (in all its forms); hydroelectricity; tidal power; wind energy; wave energy; and deep geothermal energy. Beautiful illustrations augment the text, while tables, boxed examples and online end-of-chapter exercises enrich your learning experience. New to this edition: a new chapter on thermodynamics provides a useful primer for understanding renewable heat energy technologies; an updated chapter explores the status of challenges and opportunities for the integration of renewable energy technologies in rapidly evolving electric grid systems; a new chapter on renewable energy futures looks ahead to potential developments in this ever-advancing field; [and] enhanced pedagogy that includes more comprehensive chapter summaries"-- Page 4 of cover.